Constituting China: the role of metaphor in the discourses of early Sino-American relations - Blanchard, Eric M (Journal of international relations and development, 2013)
This paper demonstrates the value of political metaphor analysis as a tool for answering constitutive questions in International Relations (IR) theory, questions that attend to how the subjects of international politics are constituted by encounters with other subjects through representational and interactional processes. To this end, I examine the key metaphors within American political discourse that guided and structured early Sino-American interactions, focusing on US Secretary of State John Hay's Open Door notes and the contemporaneous Chinese Exclusion Acts. Viewed from a social constructivist metaphor perspective, this metaphorical protection of free trade and great power privilege hid the assumption that China was unable to act as its own doorkeeper, obscuring debates in the domestic and international spheres as to the meaning of ‘Chinese’ and the appropriate strategy for managing the encounter. A second approach, the cognitive perspective, builds on the seminal IR applications of cognitive linguistics and cognitive metaphor theory to reveal the deeper conceptual basis, specifically the CONTAINER schema, upon which this encounter was predicated. Used in tandem, these two approaches to the constitutive role of political metaphor illuminate the processes by which metaphors win out over competing discourses to become durable features of international social relations.